2017
DOI: 10.1016/j.clnu.2016.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic resistance assessed by oral stable isotope ingestion following bed rest in young and older adult volunteers: Relationships with changes in muscle mass

Abstract: Bed rest-induced AR is much greater in the older than in younger adults. We have developed a new, simple, non-invasive method for the assessment of AR. The results indicate that this metabolic abnormality is a key mechanism for sarcopenia of aging and inactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 18 publications
0
35
0
Order By: Relevance
“…Of 67 records identified through search query and two identified through other sources, 45 were excluded from title and abstract, while the remaining 24 were downloaded for a deeper assessment. Finally, a total of 18 articles matched the topic at issue …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of 67 records identified through search query and two identified through other sources, 45 were excluded from title and abstract, while the remaining 24 were downloaded for a deeper assessment. Finally, a total of 18 articles matched the topic at issue …”
Section: Resultsmentioning
confidence: 99%
“…Functional anisotropy and T 2 relaxation time were also proposed to investigate muscle quality. Indeed, increased fractional anisotropy values in the bilateral quadriceps muscles were observed by Melville et al in a patient with sarcopenia, while increased T 2 values were found and in frail/prefrail subjects affected by sarcopenia …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations